2017
DOI: 10.1111/scs.12484
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive effects between cognitive stimulation and reminiscence therapy on cognitive function and quality of life for different types of behavioural problems in dementia

Abstract: This study suggests that CST and RT could be applied to improve the cognitive function and quality of life for PwD, as well as contribute to the effectiveness of nonpharmacological approaches to PwD with certain types of behavioural problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…The activity and the principles of this CST-M could mediate significant changes in the cognitions. This result is aligned with the findings from previous studies regarding the effect of CST-M on improving cognitive functions among older people (Woods et al, 2012;Aguirre et al, 2013;Lin et al, 2018;Sarageh et al, 2022). The program provides meaningful and person-centred activities for the participants.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The activity and the principles of this CST-M could mediate significant changes in the cognitions. This result is aligned with the findings from previous studies regarding the effect of CST-M on improving cognitive functions among older people (Woods et al, 2012;Aguirre et al, 2013;Lin et al, 2018;Sarageh et al, 2022). The program provides meaningful and person-centred activities for the participants.…”
Section: Discussionsupporting
confidence: 92%
“…Findings from the study suggested that the CST-M programme improved most components in the domain of cognitive functions, especially orientations, thinking operation, visuomotor organisation and memory among older people with mild dementia in the institution. The improvement in cognitive functions are aligned with the findings from previous literature regarding the effect of CST on improving cognitive functions among older people (Woods et al, 2012;Aguirre et al, 2013;Lin et al, 2018;Sarageh et al, 2022). It is postulated that the changes in cognitions are results of the enriched environment and sensory stimulations in the activity that may induce hippocampal neurogenesis, an increase in synaptic plasticity and density, an increase in the alpha wave in addition to the decrease of cortisol during engagement in the activities as suggested in the previous study (Carrion et al, 2018;Chalfont et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies indicate that CST improves cognitive functions (Gibbor et al, 2021;Sarageh et al, 2022;Dahlan et al, 2022;Wood et al, 2023), Mood (Chen, 2022) and quality of life (Gibbor et al, 2021;Wood et al, 2023) and the effect can be maintained after three months (Lin et al, 2018). In addition, CST could reduce depression among older people with dementia (Sarageh et al, 2022;Wood et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 96%
“…16 In the process of remembering, 'living in the past' is used as a dynamic adaptation process without this being considered a problem. 17 In this respect, reminiscence therapy should be used to enable older individuals to share their life experiences and thus experience a greater degree of psychological empowerment. 18 Psychiatric nurses, who play an important role in protecting and improving community mental health, should undertake interventions that support on-site ageing while providing geropsychiatric care.…”
Section: Introductionmentioning
confidence: 99%